Ultrasonic neuromodulation mediated by mechanosensitive ion channels: current and future - Song, Mengyao; Zhang, Mingxia; He, Sixuan; Li, Le; Hu, Huijing (Frontiers in Neuroscience, 2023)
Ultrasound neuromodulation technology is a promising neuromodulation approach, with the advantages of noninvasiveness, high-resolution, deep penetration and good targeting, which aid in circumventing the side effects of drugs and invasive therapeutic interventions. Ultrasound can cause mechanical effects, activate mechanosensitive ion channels and alter neuronal excitability, producing biological effects. The structural determination of mechanosensitive ion channels will greatly contribute to our understanding of the molecular mechanisms underlying mechanosensory transduction. However, the underlying biological mechanism of ultrasonic neuromodulation remains poorly understood. Hence, this review aims to provide an outline of the properties of ultrasound, the structures of specific mechanosensitive ion channels, and their role in ultrasound neuromodulation.